Forging Latin America : profiles in power and ideas, 1492 to today - Crandall, Russell, 1971- (Rowman & Littlefield, 2024)
"An exploration of Latin America's political history, this book profiles fifty-two of the region's most influential figures-from dictators and reformers to artists and priests-who, for better or worse, have shaped its character and destiny from the Spanish Conquest to the present day"--